2018
DOI: 10.18393/ejss.467595
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of mercury distribution in the soils around gold mining area at Dar-Mali locality, river Nile State, Sudan

Abstract: An artisanal gold mining region located in North of Atbara (Dar-Mali locality), River Nile State, Sudan (17.82289 to 17.82389N and 33.99974 to 34.02127E) has been studied with the aim to evaluate the soil contamination with mercury (Hg) using two parameters; (i) Comparison of the Hg concentration with the mean concentrations in world soils, (ii) Enrichment Factor (EF). The results revealed that, the concentrations of the Hg are varying in the studied area and the highest concentrations were obtained inside the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The contamination of the soils of this mining area and the nearby soils is due to the direct spillage during the amalgamation, the wet and dry deposition of the atmosphere, and the runoff of the residues. Again the work of Donkor et al (2006), who also worked in a mining area in Ghana, did not fully confirm the findings made by Okang ' Odumo et al (2014), Ali et al (2018) and Ikingura et al (1997); but the presence of Hg was reported in the soils of areas near the mine site, and large concentrations of THg (4.876 mg.kg -1 dw) and MeHg (0.162 mg.kg -1 dw) were found during the wet season in the soils of the mine site. MeHg was undetectable in soil samples during the dry season, which would be due to the low water content of these soils during the dry season, thus limiting the microbial activities that allow the production of MeHg (Donkor et al, 2006).…”
Section: Mercury In the Atmosphere And In The Terrestrial Ecosystemmentioning
confidence: 68%
See 4 more Smart Citations
“…The contamination of the soils of this mining area and the nearby soils is due to the direct spillage during the amalgamation, the wet and dry deposition of the atmosphere, and the runoff of the residues. Again the work of Donkor et al (2006), who also worked in a mining area in Ghana, did not fully confirm the findings made by Okang ' Odumo et al (2014), Ali et al (2018) and Ikingura et al (1997); but the presence of Hg was reported in the soils of areas near the mine site, and large concentrations of THg (4.876 mg.kg -1 dw) and MeHg (0.162 mg.kg -1 dw) were found during the wet season in the soils of the mine site. MeHg was undetectable in soil samples during the dry season, which would be due to the low water content of these soils during the dry season, thus limiting the microbial activities that allow the production of MeHg (Donkor et al, 2006).…”
Section: Mercury In the Atmosphere And In The Terrestrial Ecosystemmentioning
confidence: 68%
“…Therefore, the presence of Hg in the areas close to the artisanal gold mining site would be due to the dry deposition process (Ali et al, 2018). However, the concentration of Hg in the sites studied is above the average global concentrations in soils, and this does not exclude the closure of this area to carry out decontamination work (Ali et al, 2018). Podolský et al (2015) measured mercury in the soils of the extraction and smelting zones of certain metals in Namibia and Zambia.…”
Section: Mercury In the Atmosphere And In The Terrestrial Ecosystemmentioning
confidence: 98%
See 3 more Smart Citations